Divine Causation God Acts with Good Reasons - Hess, Keith (2023)
This essay introduces Philosophia Christi's symposium on the book, Philosophical Essays on Divine Causation, edited by Greg Ganssle. A short review of each essay in the symposium follows. A call is given for Christian philosophers to take divine causation into account while doing research in their primary area of philosophy. These updated and expanded essays were first presented in a more limited form at the 2023 Pacific Division Meeting of the American Philosophical Association.
Keywords: Rezension